2009
DOI: 10.1017/s0025315408003159
|View full text |Cite
|
Sign up to set email alerts
|

Stress level in wild harbour porpoises (Phocoena phocoena) during satellite tagging measured by respiration, heart rate and cortisol

Abstract: During satellite tagging of harbour porpoises (Phocoena phocoena), heart rate, respiration rate and cortisol value were measured to evaluate stress effects during handling and tagging. Respiration rates were obtained using video recordings, heart rates were recorded and serum cortisol levels were analysed from blood samples. Differences in heart rates, respiration rates and cortisol levels before and during the tagging events were investigated. An overall significant decrease of 31.5% in respiration rate was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 21 publications
2
37
0
Order By: Relevance
“…Differences were noted between sexes only for the innermost blubber layer; however, the small sample size for females precludes a complete assessment of the influence of sex on cortisol. Results in the literature regarding sex differences in cortisol are mixed in marine and terrestrial mammals, with some documenting differences among sexes in polar bears (Oskam et al 2004;Macbeth et al 2012) whereas others found no differences in polar bears, grizzly bears, and harbour porpoises (Eskesen et al 2009;Macbeth et al 2010;Bechshoft et al 2013). The higher cortisol levels in the metabolically active inner blubber layer of females compared to males may be a reflection of higher stress conditions or energetic demands in reproductive females (Macbeth et al 2012 and references therein).…”
Section: Cortisol Levels and Variabilitymentioning
confidence: 99%
“…Differences were noted between sexes only for the innermost blubber layer; however, the small sample size for females precludes a complete assessment of the influence of sex on cortisol. Results in the literature regarding sex differences in cortisol are mixed in marine and terrestrial mammals, with some documenting differences among sexes in polar bears (Oskam et al 2004;Macbeth et al 2012) whereas others found no differences in polar bears, grizzly bears, and harbour porpoises (Eskesen et al 2009;Macbeth et al 2010;Bechshoft et al 2013). The higher cortisol levels in the metabolically active inner blubber layer of females compared to males may be a reflection of higher stress conditions or energetic demands in reproductive females (Macbeth et al 2012 and references therein).…”
Section: Cortisol Levels and Variabilitymentioning
confidence: 99%
“…Harbour porpoises were incidentally caught in pound net fishery and tagged within 36 h of being discovered by the fisherman. An Argos satellite transmitter was attached to the dorsal fin of each harbour porpoise using one, two or three 5 mm diameter polyoxymethylene pins covered with silicone tubing (for more details on tagging procedure, transmitters and effects of tagging, see Eskesen et al, 2009;Geertsen et al, 2004;Teilmann et al, 2007;Sveegaard et al, 2011). For photos of an attached transmitter see Sonne et al (2012).…”
Section: Satellite Telemetrymentioning
confidence: 99%
“…Although stress reactions occur naturally throughout an individual's life due to, for example, social competition, breeding behaviour, or environmental demands, anthropogenic factors such as vessel traffic, noise, fishing, and chemical pollution can act as significant stressors and negatively impact the health of cetaceans (St. Aubin & Dierauf, 2001;Eskesen et al, 2009). During stress reactions, neurologic, endocrinologic, and immunologic changes take place, and if the animal is unable to adapt to the stressful event, deleterious effects or death may occur (Moberg, 1987;St.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, adrenocorticotropic hormone (ACTH), catecholamines (adrenaline, noradrenaline, dopamine), and the thyroid hormones triiodothyronine (T3) and thyroxine (T4) were studied. Data on cortisol obtained parallel to this study were already published in Eskesen et al (2009) for free-ranging harbor porpoises and in Desportes et al (2007) for harbor porpoises in human care. These results are cited here for statistical analysis in search of relationships with blood organochlorine concentrations.…”
Section: Introductionmentioning
confidence: 99%